EOSINOPHILS PROFILE AND LUND-MACKAY SCORE OF NASAL POLYPS IN ARIFIN ACHMAD HOSPITAL, RIAU PROVINCE - Yolazenia Yolazenia; Inayah Inayah; Febri Romaito Romaito; Retni Tri Handayani; Novisa Dwi Utami (Berkala Kedokteran, 2022)
Abstract: Theories suggest that nasal polyps occur as a result of chronic inflammation of the nasal and sinus mucosa. Eosinophils are the main inflammatory cells found in nasal polyp tissue. The severity of nasal polyps can be seen from the CT Scan of the Paranasal Sinus (PNS) using the Lund-Mackay score. The purpose of this study was to determine the description of the eosinophil count of nasal polyp tissue and the Lund-Mackay score of CT Scan PNS of nasal polyps patients in Arifin Achmad Hospital, Riau Province. Examination of the eosinophil count was carried out microscopically using histopathological preparations of nasal polyp tissue with semiquantitative assessment, and Lund-Mackay score was assessed from the CT Scan of the PNS. From the 14 samples collected, there were 8 men (57.1%) more than 6 women (42.9%) with an average age of 30.43 ± 17.36 years old. Eosinophil counts were obtained in 5  (35,7%) samples 1/2+,  5 (35.7%) samples 1+, and negative in 4 samples (28,6%). While the Lund-Mackay score obtained an average value of 10.21 ± 6.87 with a low category in 11 (78.6%) and high in 3 (21.4%) samples. Patients with high Lund-Mackay scores tend to have higher eosinophil counts which reflect a more severe degree of disease severity in nasal polyps.Keywords: Eosinophil; Lund-Mackay Score; Nasal polyp; Paranasal sinus